Gerakan Pembangunan Desa Semesta Nasional Melalui Pemberdayaan Gapoktan Padangan Dalam Pengelolaan Limbah - Hardo Wahyudi; Surya Priyambudi; Ahmat Firmansyah; Joko Slamet; Yulinda Prastika (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2020)
Randupadang Village is one of the villages located in Menganti District, Gresik Regency. The main agricultural commodities in this village are rice and corn. In addition, this village has a farmer group (gapoktan) which manages the farm of 9 dairy cows. All cows are kept in a semi-permanent cage, so that approximately 135 kg of cow dung every day must be cleaned in order to have a clean condition cage. Unfortunately, cow dung waste has not been utilized optimally. The society there prefer to dump it into the river or around the cage. It is caused by lacking of knowledge and public awareness. As a result, environmental pollution, including land, water and air, has made the image of the village less clean. The methods implemented by the team to reduce these problems are: counseling, FGD and assistance in making liquid fertilizer (POC) and compost from cow dung waste as basic ingredients. The results of this activity Gapoktan Padangan: 1) The establishment of a centralized waste treatment unit, 2) The establishment of an independent village in waste treatment, 3) The improvement of community welfare. 4) There was an skills increase 69.56% increase in making liquid fertilizer (POC) and 65.22% in making compost. The waste management of Gapoktan Padangan based on empowerment program is an effort to support ‘Desa Semesta Nasional’ development movement, which is one of the government programs in realizing an independent village based on community and local natural resources